2016
DOI: 10.18632/oncotarget.8934
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant modified TPF (docetaxel, cisplatin, fluorouracil) for patients unfit to standard TPF in locally advanced head and neck squamous cell carcinoma: a study of 48 patients

Abstract: TPF (docetaxel, cisplatin, fluorouracil) is the standard chemotherapy used for induction in locally advanced head and neck squamous cell carcinoma (LAHNSCC).Its toxicity limits it to younger patients with good functional status and without significant comorbidity. Since modified TPF (mTPF) demonstrated higher tolerability with similar efficacy in gastric cancer, we tested this scheme on frail patients.From July 2010 to July 2014, the files of the 48 patients treated for LAHNSCC with mTPF in three French instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…A retrospective study from J Fayette et al in France used the modified TPF regimen of docetaxel and cisplatin at 40 mg/2 on day 1 and a bolus of 5FU at 400 mg/m2, then 1000 mg/m2 on Day 1-2 every 2 weeks. The authors reported 10% of febrile neutropenia, 83% of overall response rate and 19% of complete response [22]. Notably, the regimen adopted by J Fayette et al was similar to that our study used, such as biweekly administration, and 48-h infusion of high-dose 5FU.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A retrospective study from J Fayette et al in France used the modified TPF regimen of docetaxel and cisplatin at 40 mg/2 on day 1 and a bolus of 5FU at 400 mg/m2, then 1000 mg/m2 on Day 1-2 every 2 weeks. The authors reported 10% of febrile neutropenia, 83% of overall response rate and 19% of complete response [22]. Notably, the regimen adopted by J Fayette et al was similar to that our study used, such as biweekly administration, and 48-h infusion of high-dose 5FU.…”
Section: Discussionsupporting
confidence: 74%
“…Toxicity is a major issue of ICT, with up to 6% toxic deaths and 11% of febrile neutropenia [ 4 , 20 ]. Some studies had tried to find fewer toxic regimens by reducing chemotherapy dose [ 21 , 22 ]. HM.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were treated with TPF chemotherapy. The treatment procedure was as described previously 35 – 37 . Briefly, we performed three 21-day cycles of induction chemotherapy with docetaxel (75 mg/m 2 continuous i.v.…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30] Other authors have limited its use to patients with good general condition including performance status 0 or 1, weight loss d" 10%, absence of severe comorbidities, < 70 years of age. 31 These data suggest that definitive CCRT should remain the standard of care while ICT should be reserved for patient population likely to receive greatest benefit from this strategy. 32,33 Conclusions The debate regarding the role of ICT in head and neck cancer is an open topic for discussion among the oncology fraternity for more than a decade now.…”
Section: Role Of Ict In Present Scenariomentioning
confidence: 96%